2000
DOI: 10.1007/s001250051351
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of adenoviral-mediated superoxide dismutase gene transfer to the reduction in nitric oxide-induced cytotoxicity on human islets and INS-1 insulin-secreting cells

Abstract: It has been established from numerous studies that oxygen and nitrogen free radicals can contribute to the islet beta-cell destruction in Type I (insulin-dependent) diabetes mellitus models [1±2]. The deleterious actions of activated mononuclear cells could be mediated by cytokines through an increase in the intracellular generation of superoxide anions, nitric oxide (NO) and peroxynitrite [3±5]. Islet beta cells appear to have an exquisite sensitivity to these radicals because of constitutively low expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Others, however, studied the protection of CuZn-sod against hypoxia-reoxygenation damage, which is also free radical mediated. 14,18,32,33 In the present experiment, significant levels of CuZnsod were produced in NeRCaMs at the third day of infection with AdCuZn-sod compared to noninfected cells. However, the occurrence of cellular cytotoxicity limited the MOI of AdCuZn-sod to 25 PFU/cell.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Others, however, studied the protection of CuZn-sod against hypoxia-reoxygenation damage, which is also free radical mediated. 14,18,32,33 In the present experiment, significant levels of CuZnsod were produced in NeRCaMs at the third day of infection with AdCuZn-sod compared to noninfected cells. However, the occurrence of cellular cytotoxicity limited the MOI of AdCuZn-sod to 25 PFU/cell.…”
Section: Discussionsupporting
confidence: 46%
“…CuZn-sod activity increased two and eight folds in A549 cells infected with an MOI of 20 and 50 of AdCuZn-sod at the third day postinfection, respectively. 18 Others showed a 2-3-fold increase in the activity of CuZn-sod in islets 33 and aortic endothelial cells 34 3 days postinfection.…”
Section: Discussionmentioning
confidence: 96%
“…RNA extraction was performed using the RNA NOW-LM kit (Biogentex, Seabrook, TX). Synthesis of first-strand cDNA was performed from DNase-treated RNA (DNase I; Gibco-BRL), using the SuperScript II RT kit (Gibco-BRL), with 25 ng/l oligo(dT) [12][13][14][15][16][17][18] as primer. The RT product was amplified by PCR in the LightCycler, which allows real-time quantification of the PCR product, based on the incorporation of a fluorescent dye in the neosynthesized DNA and its measurement at the end of each PCR cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation can not only functionally impair or reduce the mass of implanted islets but can also result in the amplification of the subsequent immune response in a transplantation setting. In the transplanted islets, the induction of cytoprotective genes that are capable of scavenging oxygen radicals and preventing the toxic effects of proinflammatory cytokines might therefore promote early function (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…However, LWE treatment caused an increase in the activity of these antioxidant enzymes in HIT-T15 cells, indicating that LWE reduced SIN-1-induced oxidative stress. A number of studies have reported that the overexpression of CuZnSOD had a protective effect in NO-induced human islets, INS-1 insulin-secreting cells (28) and alloxan-and streptozotocin-induced diabetes (29,30). CAT has also exhibited a protective effect against H 2 O 2 and streptozotocin-induced oxidative stress in vivo (31).…”
Section: Discussionmentioning
confidence: 99%